Strategi Manajemen Sebagai Faktor Mitigasi Dalam Penerimaan Opini Audit Studi Empirik pada Perusahaan Manufaktur di Indonesia - Widhy Setyowati (MAKSIMUM, 2014)
This research aims to provide emprical evidence upon the research questions proposed by conducting measurement of the hypothesis on the influence of the management strategy as mitigation factor in predicting the acceptance of GCO that involves financial based strategy such as sale of common stock strategy, issuing new debt restructure, and sale of fixed asset. Whereas, non financial strategy  that is expansionist and oriented to external market  that will be studied as mitigation factor includes cooperative strategy or long term contract strategy and new product development strategy or expansion of new market segment. The result show that the sale of common stock strategy and issuance of new debt or restructuring of debt strategy are the mitigation factors in acceptance of going concern opinion, whereas reducing cost strategy  are perceived as additional going concern risk factors and increase the likelihood to receive a going concern opinion. Other strategies such as disposed fixed asset strategy, cooperation/long-term contracted streategy and development new product/expanding new market segments can not be used to predict the acceptance of going concern opinion.Keywords : going concern opinion, financial distress, management strategy, mitigation factor